Pengaruh Tingkat Pendidikan terhadap Kemiskinan di Kota Kupang Nusa Tenggara Timur - Ghale, Antonia Jesica Dadi; Elaman, Godeliva Mega Putri Tuto; Bana, Evangeli Cindy; Iri, Gratia Kontar; Jemahan, Maria Jenifer Da Costa; Teti, Theresa Apriani; Lawalu, Emiliana Martuti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Poverty remains a persistent and complex problem in Kupang City, East Nusa Tenggara, characterized by low income levels, high unemployment rates, and limited access to education. This study aims to examine the impact of educational attainment on poverty levels among low-income communities in Kupang. Utilizing a qualitative research approach, data were collected through structured interviews with 15 respondents aged 15 to 50, supported by literature review and secondary data from government reports. The study applies the Miles and Huberman interactive model for data analysis, emphasizing data condensation, display, and conclusion drawing. Findings reveal that low educational attainment significantly contributes to the high poverty rate in the region. Individuals with limited education often face difficulties in securing stable employment, reinforcing cycles of poverty and school dropouts. Moreover, a lack of awareness about the importance of education and insufficient government intervention exacerbates the issue. Respondents expressed concerns about limited infrastructure, high education costs, and the absence of inclusive empowerment programs. The study concludes that improving educational access and awareness is critical to breaking the poverty cycle. It recommends a collaborative strategy involving government, communities, and private stakeholders to implement sustainable educational and economic interventions tailored to local needs.